Analisis Sentimen Pengunjung Wisata Heritage Kota Semarang Menggunakan Naive Bayes Pada Ulasan Google Maps - Cherlina Helena P Panjaitan, Candra Supriadi (Jurnal Elektronika dan Teknologi Informasi, 2023)
Semarang, as the capital of Central Java Province, has several heritage tourist attractions, namely tourism that uses a place or area that has history and an important role in a region as a tourist destination, one of the historical building which is considered a cultural heritage. One of the famous cultural heritage sites in Semarang is Lawang Sewu. Also there are Museum Kota Lama which was just opened by the Semarang city government in 2022, then Sam Poo Kong which is one of the oldest monasteries and cultural tourist attractions in Semarang. An analysis of the sentiment of visitors to heritage tourism through reviews on Google Maps will be carried out to find out whether the tourist attraction is considered positive or negative in the public's view. These three tourist attractions are heritage tourist destinations in Semarang City which are widely reviewed by the public. The aim of this research is to find out public reviews of heritage tourist destinations in Semarang City. Reviews were taken on the Google Maps site, using the Naïve Bayes classifier algorithm. In analyzing sentiment using the RapidMiner application.